EFFECTIVENESS OF GRANDAZOL IN OPERATIVE GYNECOLOGY - Геник, Н. І.; Ласитчук, О. М.; Пахаренко, Л. В.; Кінаш, Н. М.; Оріщак, І. К. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
A clinical research was conducted to study the effectiveness and tolerability of drug Grandazol compared with a combination of drugs Levofloxacin hemihydrate and Ornidazole for the prevention of inflammatory complications after gynecologic operations. The study included 78 patients who were hospitalized. They were randomized into groups at a ratio of 1: 1. Obtained results demonstrate sufficient effectiveness and good tolerability of Grandazol. Established a significant reduction of subjective and objective symptoms, acceleration time of wound healing and absence of inflammatory complications in 100% of patients while using the investigational product.